2019
DOI: 10.1016/j.jjcc.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Association between changes in platelet reactivity during elective percutaneous coronary intervention and periprocedural myocardial infarction: A pilot study

Abstract: An increase in platelet reactivity after elective PCI is possibly associated with PMI. This finding should be validated by a larger-scale study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, previous studies showed that cytochrome P‐450 genetic variants did not affect inhibition of platelet aggregation in patients treated with prasugrel 24,25 . Meanwhile, platelet reactivity has been demonstrated to affected by PCI 8,9,26 . We also reported that an increase in platelet reactivity just after elective PCI was associated with increased risk of PCI‐related myocardial infarction 26 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, previous studies showed that cytochrome P‐450 genetic variants did not affect inhibition of platelet aggregation in patients treated with prasugrel 24,25 . Meanwhile, platelet reactivity has been demonstrated to affected by PCI 8,9,26 . We also reported that an increase in platelet reactivity just after elective PCI was associated with increased risk of PCI‐related myocardial infarction 26 .…”
Section: Discussionmentioning
confidence: 70%
“…8,9,26 We also reported that an increase in platelet reactivity just after elective PCI was associated with increased risk of PCI-related myocardial infarction. 26 Additional studies showed that platelets are activated during PCI due to regional endothelial dysfunction caused by ischemia or by iatrogenic reasons. 8,9 Considering that high platelet activity influences the inflammatory status, we hypothesized that LVR may be affected by a condition with high platelet reactivity after PCI induced by both the acute myocardial infarction and the PCI procedure.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation